ANALYSIS OF POTENTIAL EFFECTIVENESS AND EFFICIENCY OF TERMINAL RETRIBUTION IN NORTH CENTRAL TIMOR REGENCY - Margareta Diana Pangastuti; Yuliati Sengkoen (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2026)
This study aims to analyze the potential effectiveness and efficiency of terminal levy revenue at the Technical Facilities Management Unit (UPTD) of North Central Timor Regency for the 2020-2024 period. The research method used is a quantitative descriptive method with an analysis approach of effectiveness, efficiency, and contribution of terminal levy revenue to Regional Original Income (PAD). The data used are secondary data in the form of targets and realization of terminal levy revenue, as well as operational costs incurred by the UPTD during the study period. The results of the study indicate that the overall level of effectiveness of terminal levy revenue still fluctuates, where in certain years it reaches the effective category, but in other years it does not meet the target. From the efficiency aspect, it was found that the use of operational costs in several years has not been fully efficient because the realization of costs is higher than the revenue. Meanwhile, the contribution of terminal levies to PAD of North Central Timor Regency is still very low, so it has not played a significant role in regional income.